Opowieść o „życiopisaniu”. Portret Emily Dickinson w filmie „Cicha namiętność” Terence’a Daviesa - Bobowski, Sławomir (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Emily Dickinson was not married nor had children, she did not establish a family, but she had a life filled to the brim with love, friendship, suffering, death, searching for God and, of course, writing poems about all these fundamental phenomena of human existence. Her poetry reveals a picture of a woman who is unusually spiritually rich, beautiful and…unhappy, living for the bigger part of her mature existence like a hermit, oftentimes being a witness of deaths of those to whom she was closest. Additionally, perhaps because of her Sapphic inclination, she could experience suffering being forced to suppress it and feeling social isolation or exclusion. On the other hand, any reader of poems by “the nun of Amherst” can sense a great blast of happiness and some ecstatic delight over the existence itself and… the possibility of expressing this delight in poems. Just life itself and poetry were the greatest passions of Dickinson among many others which profusely filled her psyche. Indeed, it is difficult to assess which of these two infatuations was stronger. That is why I used in the title of my essay a neologism: “life-writing” (“życiopisanie”), which was some time ago first employed by the Polish poet Edward Stachura in reference to his own life and poetry. Terence Davies’s movie about Emily Dickinson and her life is a real masterpiece in which the weave of the two main passions Dickinson had, their interpenetration, their ardent intimacy or simply indissolubility and unity have been shown in a deliciously suggestive way. The essay is a modest attempt at using such a way of describing things.
A Story of “Life-writing”. A Portrait of Emily Dickinson in Terence Davies’s Movie: “Quiet Passion”
Keywords: Emily Dickinson; poetry; writing; life; suffering; happiness; love; Sapphic love; motherhood; fatherhood; religion; faith; mystery of God; film structure; film composition; editing; narration; poezja; pisarstwo; cierpienie; szczęście; miłość; miłość saficka; macierzyństwo; ojcostwo; religia; wiara; tajemnica Boga; struktura filmu; kompozycja; montaż; narracja